Nickel toxicity in P. lividus embryos: Dose dependent effects and gene expression analysis. (August 2018) - Bonaventura, Rosa; Zito, Francesca; Chiaramonte, Marco; Costa, Caterina; Russo, Roberta
Abstract: Many industrial activities release Nickel (Ni) in the environment with harmful effects for terrestrial and marine organisms. Despite many studies on the mechanisms of Ni toxicity are available, the understanding about its toxic effects on marine organisms is more limited. We used Paracentrotus lividus as a model to analyze the effects on the stress pathways in embryos continuously exposed to different Ni doses, ranging from 0.03 to 0.5 mM. We deeply examined the altered embryonic morphologies at 24 and 48 h after Ni exposure. Some different phenotypes have been classified, showing alterations at the expenses of the dorso-ventral axis as well as the skeleton and/or the pigment cells. At the lowest dose used, Ni mainly induced a multi-spicule phenotype observed at 24 h after treatment. On the contrary, at the highest dose of Ni (0.5 mM), 90% of embryos showed no skeleton and no pigment cells. Therefore, we focused on this dose to study protein and gene expression patterns at 24 and 48 h after exposure. Among the proteins analyzed, i.e. p38MAPK, Grp78 and Mn-SOD, only p38MAPK was induced by Ni treatment. Moreover, we analyzed the mRNA profiles of a pool of genes that are involved in stress response and in development mechanisms, i.e. the transcription factors Pl - NFkB and Pl - FOXO ; a marker of DNA repair, Pl -XPB/ ERCC3 ; a mitogen-activated protein kinase (MAPK), Pl - p38 ; an ER stress gene, Pl - grp78 ; an adapter protein, Pl - 14-3-3ε ; two markers of pigment cells, Pl - PKS1 and Pl-gcm . The spatial expression of mesenchymal marker genes has been evaluated in Ni-treated embryos at both 24 and 48 h after exposure. Our results indicated that Ni acts at several levels in P. lividus sea urchin, by affecting embryo development, influencing the embryonic immune response and activating stress response pathways to counteract the suffered injury and to promote embryos surviving. Highlights: Ni at 0.5 mM upregulates p38MAPK, grp78, XPB/ERCC3 and NF-kB genes. PKS1 and gcm gene are down regulated by Ni at 0.5 mM. Pigment cells decrease in number or are absent in Ni-exposed embryos. Ni at 0.5 mM induces p38MAPK protein activation after 24 h of exposure. P. lividus is as a good model to study the signaling pathways activated by Nickel.